Kepemimpinan Modern Berbasis Karakter Pesantren - Hilmy, Masdar (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This article discusses the relevance and reevaluation of pesantren character education to the needs of character values ​​in modern society. This article uses a descriptive qualitative analysis of the object of discussion by utilizing reference sources on related themes. This article argues that the values on pesantren education is a prototype of character education that is still relevant to the needs of the community and, hence, can be adopted for the national leadership regeneration. The survival and the existence of salaf and khalaf pesantren that are still needed by the community indicates the relevance of pesantren-style character education. However, this article also gives a thick note that pesantren character education does not guarantee the objectivation process and the implementation of character values ​​by its alumni in real life in society. This simply because the relationship between character education in pesantren and the objectivation and implementation of character values ​​by pesantren alumni in the community is not a linear, verbatim and axiomatic relationship. Therefore, this article also offers a solution so that the education of character values ​​in pesantren must proceed side by side with the capacitation process of internal defense mechanisms and external supervision among santri.